PEMETAAN POTENSI EKONOMI UNGGULAN BERBASIS SUMBERDAYA LOKAL UNTUK PENGEMBANGAN UNIT USAHA DI DESA BOBAWA KECAMATAN MAKIAN BARAT KABUPATEN HALMAHERA SELATAN - Zulkifli,; Daud Hasim,; Karim Abubakar, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
This community service activity is aimed at providing information and accompanying the community, the management of Village Owned Enterprises (BUMDes) and the village government of West Makian Subdistrict, related to increasing the Capacity of local resource-based communities, as an effort to increase community income. Devotional activities are carried out for two months. Activities began with socialization in forming understanding in superior village business, simulation of village potential mapping and mentoring of marketing plans and targets to business feasibility. The target of devotional activities is expected in the form of increasing understanding related to the potential of local natural resources and the main development of local resource potential, BUMDes has a business development plan, to the selection of business types. This activity received a fairly good response from the village government, BUMDes Management to youth, so that the PKM target groups asked to be assisted in relation to business development in Babawae village